Monitoring demersal scalefish populations in the Browse Basin region: accounting for spatial variability and detecting change in key fish populations - Babcock, R.; Lawrence, E.; van der Velde, T.; Pitcher, C.; Tonks, M.; Bessey, C.; Harvey, Euan; Newman, Stephen (2017)
One of the objectives of the Applied Research Program (ARP), funded by Shell and the INPEX-operated Ichthys LNG Project, was to establish the basis for evaluating the effects of any potential oil spill from the Prelude or Ichthys fields on populations of commercially important demersal fishes in the Northern Demersal Scalefish Managed Fishery. The ARP has delivered improved baseline understanding of the status and spatial variability in populations of commercially and ecologically important finfish of the Browse Basin region, in the vicinity of the Prelude and Ichthys fields, using both commercial-style fish traps and baited remote underwater videos (BRUVs) as sampling methods. We used available environmental-data layers and fish-distribution data, in combination with modelled plume projections, to design a study such that sites were balanced with respect to fish habitat and likely affected and unaffected zones. The sampling-design employed was statistically effective with power to show changes in fish assemblages, and relative abundance of as little as 30% could be detected with 80% certainty in the main commercial species, goldband snapper (Pristipomoides multidens), using BRUVs. For the second-most important species, red emperor (Lutjanus sebae), a larger decline of 50% would have to occur for this change to be determined with the same level of confidence. Traps were a more powerful tool for sampling L. sebae, allowing a 40% change to be detected; however, for all other species BRUVs were more powerful. Sampling of the demersal-fish assemblages surrounding the Prelude and Ichthys fields by using both fish traps and BRUVs demonstrated the feasibility of detecting change in the relative abundance of the fish assemblage as well as in the key commercial species.